Cardiac relapse of extranodal NK/T-cell lymphoma manifesting as incessant ventricular tachycardia: a case report. Issue 9 (6th September 2022) - Kolesnik, Ewald; Stangl, Verena; Haring, Bernhard; Scherr, Daniel; Rainer, Peter P
Abstract: Background: Cardiac tumours are rare but affected patients may present with symptoms mimicking other cardiac diseases. The most frequent symptoms include heart failure, arrhythmias, or embolic phenomena. Case summary: A 39-year-old man with a history of extranodal NK/T-cell lymphoma of the nasal type (ENKTL-NT) in clinical remission presented at our department with incessant ventricular tachycardia. The arrhythmia could only be controlled with a combination of intravenously administered beta-blockers, ajmaline, and amiodarone. Diagnostic workup excluded ischaemia, but imaging revealed a tumour located in the apex of the left ventricle. Endomyocardial biopsy confirmed the diagnosis of cardiac relapse of ENKTL-NT. Upon chemotherapy no further arrhythmias developed. Discussion: Many malignancies can metastasize into the heart. Multimodal imaging including echocardiography, cardiac magnetic resonance imaging, and a positron-emission tomography computed tomography paved the way to the diagnosis that was finally established by endomyocardial biopsy. In the present case, a cardiac metastasis from an ENKTL-NT presented with incessant ventricular tachycardia.